In vitro synergistic effect of AXL, FAK and ErbB receptors inhibitors for head and neck cancer - Valeria Lucarini; Valentina Angiolini; Daniela Nardozi; Monica Benvenuto; Chiara Focaccetti; Patrizia Mancini; Elena Splendiani; Tanja Milena Autilio; Claudio Cortese; Riccardo Bei; Gianluca Nicolai; Camilla Palumbo; et al. (Biology Direct)
Abstract The prognosis for patients with head and neck cancer (HNC) is usually poor, highlighting the need for new therapeutic strategies. To this end, this study aims to evaluate the antitumor efficacy of a combined treatment with low doses of different molecular targeted drugs, i.e. Y15, a FAK inhibitor, Afatinib (AFA) an ErbB inhibitor and TP-0903, an Axl inhibitor, on HNC. Human cell lines from salivary gland, tongue and pharynx HNC, cultured in 2D and 3D (spheroids) conditions, were used to evaluate the antitumor effects of Y15, AFA and TP-0903, alone or in combination. Cell survival, death and migration were evaluated. Western blotting and immunofluorescence analysis were performed to investigate the expression and activation of proteins involved in signal transduction and epithelial to mesenchymal transition. The combined treatment with low doses of Y15, AFA and TP-0903, was more effective than the individual and dual drug treatments in reducing survival, increasing cell death and reducing migration of HNC cells. The three inhibitors in combination had a synergistic effect in reducing survival of HNC cell lines in both 2D and 3D conditions. Moreover, as compared to the individual inhibitors and their pairwise combinations, the triple drug combination was the only able to simultaneously downregulate Axl, FAK, and N-cadherin while upregulating E-cadherin expression levels. The results reported herein provide compelling preliminary evidence supporting the combined use of Y15, AFA and TP-0903 as a novel therapeutic strategy for HNCs.